Pembangunan Santripreneur Melalui Pelatihan Ide Bisnis Proll Tape di Pondok Modern Al-Ghuroba Sorong - Lilies Nurliza Agaki; Nur Intan Octavia; Nurliani Istiqomah; Riska Dwi Oktavia; Vira Tiffani Selly; Susetyowati Sofia; Karfin Karfin (Universitas 45 Surabaya, 2023)
Cassava is a food plant that can be used as both a light and heavy food preparation. Cassava is a raw material that can be processed into products to support the community's economy. This service presents about building santripreneurs through training with innovations in processed cassava products at Pondok Modern Al-Ghuroba Sorong. The aim of the activity is to provide knowledge and skills to female students to process cassava as food that has a higher selling value. The implementation method used is: 1). Observation of training places, 2). Identify training needs, 3). Training program model design, 4). Implementation of training and development programs, 5). Evaluation of service, 5). Final training report. Implementation of service activities by the production team with the Proll Tape business idea and carried out for 1 (one) day, namely on Saturday, 30 September 2023 at Pondok Modern Al-Ghuroba Sorong which is located at Jl. Flamboyan, Klasuluk sub-district, Mariat District, Sorong Regency, Southwest Papua Province. Participants took part in the activity with great enthusiasm and turned the activity into additional knowledge and skills for the female students. And Pondok Modern Al-Ghuroba Sorong is an educational institution that educates by balancing academics and skills for its students to keep up with developments